Penerapan Terapi Reminiscence pada Lansia dengan Ansietas di Desa Sungai Putih Kec.Tapung Kab. Kampar - Dahniati Dahniati; Yeni Devita; Yureya Nita; Fitry Erlin (Lembaga Pengembangan Kinerja Dosen, 2025)
Elderly people are individuals who are vulnerable to experiencing psychosocial problems, one of which is anxiety. Factors that influence anxiety in the elderly include changes in the psychological condition of the elderly. Anxiety in the elderly can be overcome with reminiscence therapy. Reminiscence therapy is a therapy that is carried out by the process of collecting a person's memories in the past, so reminiscence therapy is a suitable therapy for the elderly. The method used is a case study by providing reminiscence therapy to the elderly with anxiety. The implementation time is carried out with 3 sessions in 3 days. The research subjects were 3 people. This therapy lasted for approximately 30 minutes. The place of implementation was in Sungai Putih Village, Tapung District, Kampar Regency. The instrument for this case study used the TMAS (Taylor Minnesota Anxiety Scale) questionnaire. The results of this application can be concluded that there was a decrease in anxiety scores in the elderly after the application of reminiscence therapy for 3 consecutive days, with the highest anxiety score before the application of reminiscence therapy, namely 32, including severe anxiety. Meanwhile, the lowest anxiety score after reminiscence therapy was 8, which is normal anxiety.